PENGARUH KUALITAS FENOTIPIK DAN UKURAN TUBUH TERHADAP PENENTUAN HARGA JUAL PEDET SAPI PO KEBUMEN DI KABUPATEN KEBUMEN - Khoerul Umam; Nunur Nuraeni (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the effect of phenotypic quality and body size on the selling price of PO Cattle (Peranakan Ongole) in Kebumen Regency. The independent variables in this study include eight phenotypic characteristics, namely snout, dewlap, hump, hair around the eyes, tail, height, chest circumference, and body length. The dependent variable in this study is the selling price of calves. Data were collected through direct observation and interviews with farmers and traders at the animal market. Data analysis was carried out using multiple linear regression. The results showed that the Multiple R value of 0.313 indicated a weak correlation between phenotypic variables and the selling price of calves. The R Square value of 0.098 indicated that only 9.8% of the variation in selling prices could be explained by this regression model, while the remaining 90.2% was influenced by other factors outside the variables studied. Thus, it can be concluded that the phenotypic quality and body size of calves only have a low influence on the selling price of PO Cattle calves in Kebumen Regency. This study recommends the need for an assessment of other factors that more dominantly affect the selling price of calves, such as body weight, age, gender, and market conditions.